Pengaruh Variasi Waktu Dan Daya Microwave Pada Transesterifikasi Terhadap Kadar Rendemen Dan Densitas Biodiesel Minyak Biji Bunga Matahari Komersial - Azkandri, M.H.A.G.; Winaya, I Nyoman Suprapta; Ghurri, Ainul (Teknik Desain Mekanika, 2022)
Abstract Non-food sunflower seed oil has potential as an alternative raw material for biodiesel and microwave (electromagnetic wave) devices which are developments from manufacturing to increase the biodiesel conversion. The purpose of the research was to determine the effect of the variation in the transesterification conditions using a microwave device, namely with a length of 10 minutes, 20 minutes, and 30 minutes at 300 watts, 600 watts, and 900 watts of power at each time variation. The effects of time and microwave power on yields were observed in this research study. The research stages consisted of pre-treatment, transesterification, glycerol separation, washing, and analysis of yield levels. This research was conducted under atmospheric conditions using non-food sunflower seed oil and 99% methanol in a ratio of 4:1, an alkaline type of catalyst, 0.5M KOH using 99% methanol as a solvent, and a transesterification operating temperature of 60? and no more than 70?. The results showed that the highest yield level was at 30 minutes and 600 watts of power, which was 97.72%. Of the nine biodiesel samples, The result of the lowest density is at 30 minutes and 900 watts of power with a result of 0.806 gr/cm³.. It can be concluded that the variation of time and microwave power in transesterification can affect the biodiesel characteristics of sunflower seed oil. Keywords: Microwave Transesterification, yield biodiesel Of Non-food sunflower seed oil